Narrative Structure of Vladimir Propp's ''Nai Manggale'' Folklore from North Sumatera - Irhamni, Mutia (Enigma in Cultural, 2023)
The folklore "Nai Manggale" in terms of Vladimir Propp's narrative structure produces interpretive meaning as the identity of the people of the Tapanuli region, North Sumatera and as an oral literary heritage among the people which has been passed down and developed as a medium for the formation of local wisdom. The research uses descriptive - qualitative theory where primary data is intended as a reference that is tested, condensed and then classified. The research results show that of the 31 functions of narrative structure, the Nai Manggale folklore has nine functions, namely: The connective incident (B), First function of donor (D), Provision or receipt of magical agent (F), Recognition (Q) Exposure (Ex), Struggle (H), The initial misfortune or lack is liquid (K), Wedding (W), and Solution (S) Descriptive explanations were analyzed using Propp's scheme theory. The results of character studies in the Nai Manggale folklore were found to be as follows: Donor, Dispatcher and Princess. The conclusion of the research explains that the Nai Manggale folklore focuses on the main role of "Nai Manggale" which became the forerunner of the culture of deliberation and dancing in the Tapanuli area, North Sumatera.